Hausdorff gaps and limits - Frankiewicz, Ryszard (Studies in logic and the foundations of mathematics, 1994)
Gaps and limits are two phenomena occuring in the Boolean algebra P(& ohgr;)/fin. Both were discovered by F. Hausdorff in the mid 1930's. This book aims to show how they can be used in solving several kinds of mathematical problems and to convince the reader that they are of interest in themselves. The forcing technique, which is not commonly known, is used widely in the text. A short explanation of the forcing method is given in Chapter 11. Exercises, both easy and more difficult, are given throughout the book.